El terrorismo internacional y las prevenciones legales que el Ecuador debe hacer. - Jiménez Vergara, Leonor Jimena (2013)
"International terrorism, and legal warnings that Ecuador should do" is a theme that took it as legal research, for in the month of June of 2010, Ecuador was in the gray list FATF ( financial Action Task Force ) until the month of June 2012, the date on which our country was included permanently by the FAT, in the blacklist, as a high-risk country for the international financial system by deficiencies in legislation to prevent terrorist financing , circumstances under which this research I have aimed to reform in our law article that punishes the crime of terrorism, defining it properly to properly punish this offense, and also create another article to sanction financing of international terrorism. For these reasons I suggest that the first chapter covers the problem, consisting of the introduction, problem, problem formulation, justification, general and specific objectives, hypothesis, variables and resources. The second chapter refers to the theoretical framework, the components comprising the background of the research topic, the foundation in doctrine, jurisprudence, law, and comparative law. The third chapter consists of the methodology, which in turn covers the determination of the methods to be used, the research design, population and sample, techniques and tools of research, validity and reliability of the instruments, processing techniques and analysis. The fourth chapter includes the analysis and interpretation of results, interviews. The fifth chapter includes the testing of the hypothesis. In the sixth chapter, are the conclusions and recommendations made based on the outcome of the investigation, and the last chapter seven, is structured by the proposal, with the following scheme: Title, background, rationale, synthesis of diagnosis, overall objectives and specific beneficiaries, and social impact.